Disease progression in patients with usual interstitial pneumonia and probable UIP patterns on computed tomography with various underlying etiologies: a retrospective cohort study - Yang, Shuqiao; Wang, Jing; Sun, Di; Wang, Yiran; Xue, Changjiang; Ye, Qiao (Frontiers in Medicine, 2023)
Background Usual interstitial pneumonia (UIP) is a pattern of interstitial pneumonia that is caused by different etiologies. This study aimed to investigate the transplant-free survival (TFS) and the decline in forced vital capacity (FVC) of the patients with UIP and probable UIP patterns on CT caused by various underlying conditions. Methods A retrospective cohort study was conducted, enrolling patients with interstitial lung disease exhibiting a CT pattern consistent with UIP or probable UIP. Clinical and prognostic data of patients categorized by the etiology were compared. Results A total of 591 patients were included and classified into the following groups: idiopathic pulmonary fibrosis (IPF) (n = 320), connective tissue disease (CTD)-UIP (n = 229), asbestosis-UIP (n = 28), and hypersensitivity pneumonitis (HP)-UIP (n = 14). Advanced age, elevated levels of serum cytokeratin fraction 21-1 and percentage of neutrophils in bronchoalveolar lavage were observed in all groups. IPF patients showed a more rapid decline in FVC (133.9 mL/year) compared to CTD-UIP (24.5 mL/year, p = 0.001) and asbestosis-UIP (61.0 mL/year, p = 0.008) respectively. Sub-analysis of CTD-UIP revealed that patients with rheumatoid arthritis (RA)-UIP (88.1 mL/year) or antineutrophil cytoplasmic antibody-associated vasculitis (AAV)-UIP (72.9 mL/year) experienced a faster deterioration in FVC compared to those with primary Sjögren’s syndrome (pSS)-UIP (25.9 mL/year, p < 0.05). Kaplan–Meier curves showed that IPF had the poorest TFS (median 55.9 months), followed by HP-UIP (57.5 months), CTD-UIP (66.7 months), and asbestosis-UIP (TFS not reached). RA-UIP or AAV-UIP did not exhibit any prognostic advantages compared to IPF, while asbestosis-UIP and pSS-UIP showed better survival rates. Conclusion Patients with UIP caused by different underlying conditions share certain common features, but the trajectories of disease progression and survival outcomes differ.